2022
DOI: 10.3390/ijerph19127483
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Multicomponent Intervention on Daily Functioning among the Community-Dwelling Elderly: A Systematic Review

Abstract: The deterioration of physical and cognitive functioning in the elderly is an impairment to their independent self-management and to improving their ability to perform daily functions. Nurses should support the elderly to experience a healthy and a successful aging process by preventing dependence on daily functioning and understanding the care assistance that such persons need. This study aimed to gain insight into the evidence on the effectiveness of multicomponent intervention on the activities of daily livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Furthermore, an increasing trend of the global older population can be predicted to increase the number of older adults with ADL/IADL disabilities. A recent systematic review study reported that disability can be improved through individually customized interventions [31], especially focusing on the modifiable factors of ADL/IADL disability, such as physical activity, depression, and abnormal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increasing trend of the global older population can be predicted to increase the number of older adults with ADL/IADL disabilities. A recent systematic review study reported that disability can be improved through individually customized interventions [31], especially focusing on the modifiable factors of ADL/IADL disability, such as physical activity, depression, and abnormal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, IADL limitations have been verifiably improved by changing situational and environmental factors to support, rather than undermine, the physical health of older adults [ 13 ]. A recent systematic review reported that multicomponent intervention (e.g., physical therapy, memory training, occupational therapy) are effective in improving IADL limitations in the short term (three months) as well as in the long term (12 months) [ 18 ]. Accordingly, it is necessary to establish active intervention plans including environmental modifications such as function-based housing to delay the onset of IADL limitations and to improve functional limitations as much as possible among older community- residing adults.…”
Section: Discussionmentioning
confidence: 99%
“…These various factors influence deterioration of functional ability, including modifiable as well as non-modifiable factors. In particular, modifiable factors such as nutritional status, FOF, grip strength, and depression can be improved through a preventive approach [ 18 ], which is important for developing health policy in sociopolitical contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the population of older adults has been variously defined as 60 years old [ 13 ], over 65 years of age or older [ 9 ], or 80 years of age or older [ 12 ]. Interventions have targeted people living in nursing homes [ 16 ], Australian residential aged care facilities [ 17 ], and community-dwelling older people [ 10 , 17 , 18 ]. The focus has tended to be on secondary prevention, within the context of disease management, rather than primary prevention with community-dwelling adults [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 7 of the 11 reviews were about discrete topics, that is, older adults’ occupations in heatwaves [ 21 ], joy among older people [ 22 ], quality of life [ 16 , 23 ], e-tools for transportation planning [ 24 ], occupational therapy in residential aged care [ 17 ], and instruments to support occupational therapy practice [ 9 ]. A review by Kim et al [ 18 ] focused on daily functioning and included occupational therapy, but its focus was on activities of daily living and instrumental activities of daily living rather than the broader concept of healthy aging. A scoping review by Mehrotra et al [ 20 ] about healthy aging and occupational therapy in South Asian countries was potentially replicable for a wider population, but the full report is not available and the authors of the protocol have not responded to requests for the full report.…”
Section: Introductionmentioning
confidence: 99%